Mobilization and Control: Ethnic Political in Local Parliament Members Election in Indonesia - Rochadi, Af Sigit; Fawzia, Diana; Razuni, Ganjar (Universitas Negeri Semarang, 2024)
This research aims to describe and analyze the mobilization and control of ethnic ties in politics.Ethnic mobilization is prevalent in the era of Indonesian democracy, specifically at local level, as evidenced by the increasing demands for forming new autonomous regions. Various regions implement restrictions on labor externally and prioritize local ethnicities to become civil servants. These phenomena give rise to paguyuban, showing ethnic communities, and political mobilization. Therefore, this study aimed to discuss the phenomena of ethnic mobilization in Batam City, Indonesia. The city has become an industrial region crowded with local and foreign companies, exhibiting contrasting phenomena, such as industrialization, democracy, and ethnic mobilization. Data was collected by interviewing leaders of the North Sumatra Family Association ethnic community, Chair of the Malay Traditional Institution, East Java Community Association, leaders of political parties and members of local parliament (Golkar Party, PDIP, PKS, PSI). The result showed that ethnic mobilization in Indonesian local political occurs by activating differences through politicians. Paguyubans are controlled by leveraging ties, indebtedness, and money political. It persists due to the inheritance from the Dutch colonial government, decentralization that motivates the diversification of local elites, and the needs of local elites to attain political positions. Furthermore, ethnic political is not a phenomenon unique to new democratic states, necessitating a reevaluation of mobilization theories within nations.